Management Arrangement, Human Resources, and Accountability in Improving the Quality of Services at the Community and Village Empowerment Office (DPMD) of South Halmahera Regency - Sukur Suleman; Sumitro Syawal; M. Sofyan Z. Selang (Journal of Research in Social Science and Humanities, 2025)
The bureaucracy within the Community and Village Empowerment Office (DPMD) of South Halmahera Regency presents significant challenges related to the complexity of administrative systems. The most urgent issues requiring restructuring involve unclear and unmeasured systems, processes, and work procedures; an underdeveloped service culture; an organizational structure that does not align with the service mission; and low professionalism and human resource quality. Furthermore, the bureaucratic structure remains oriented toward control and authority rather than service delivery. The distribution of authority tends to be partial, not comprehensive, and rationality and professionalism remain far from expectations.This study aims to analyze how management arrangements, human resource (HR) capacity, and accountability contribute to improving public service quality at DPMD South Halmahera. The research employs a qualitative descriptive method using a case study approach. Data were obtained through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, which includes data collection, reduction, display, verification, and conclusion drawing.The results show that management arrangements at DPMD have not yet operated optimally, as evidenced by overlapping duties and weak inter-departmental coordination. Most HR personnel do not yet meet the required qualifications and need continuous competency development, especially in technology and digital service delivery. In terms of accountability, reporting mechanisms lack transparency, and supervision and evaluation are not conducted systematically and comprehensively. Overall, the quality of public service delivery at DPMD still requires improvement through better management systems, HR capacity development, and stronger, participatory accountability mechanisms.